Management science in hospitality and tourism : theory, practice, and applications - Uysal, Muzaffer; Sirakaya-Turk, Ercan; Schwartz, Zvi (Oakville, ON, Canada : Apple Academic Press, 2016)
"Management Science in Hospitality and Tourism is a timely and unique book focusing on management science applications in tourism and hospitality settings. The academic scope of management science in today's world is rather interdisciplinary and not always necessarily quantitative. The books includes such topics as: quantitative approach to tourism systems; monitoring and forecasting tourist activities; measuring forecasting accuracy in hospitality; big data analytics and information system; best-worst scaling method; partial least squares structural equation modeling (PLS-SEM); demand analysis in tourism; frontier approaches to performance measurement in hospitality and tourism; evidence-based analytics for productivity measurement; capacity management using time series; gravity model; shift-share analysis; destination attractiveness and performance measures; overbooking research in hospitality; tourist satisfaction, an index approach; general performance measures in hospitality."--
1. Management science applications in tourism and hospitality / Muzzaffer Uysal, Zvi Schwarts, and Ercan Sirakaya-Turk -- 2. Complex tourism systems : a quantitative approach / Rodolfo Baggio and Giacomo Del Chiappa -- 3. Monitoring and forecasting tourist activities with big data / Bing Pan and Yang Yang -- 4. Micro marketing and big data analytics : an information system for destination marketing management / Daniel R. Fesenmaier, Neeraj Bharadwaj, Jason Steinmetz, and Zheng Xiang -- 5. Best-worst scaling method : application to hospitality and tourism research / Eli Cohen and Larry Lockshin -- 6. Using partial least squares structural equation modeling (PLS-SEM) in tourism research / Rob Hallak and Guy Assaker -- 7. Quantity and quality issues in demand for tourism / Aliza Fleisher -- 8. Time series models for capacity management in the hospitality industry / Tianshu Zheng -- 9. An extended gravity model : applying destination competitiveness / Jeong-Yeol Park and SooCheong (Shawn) Jang -- 10. Efficacy of static shift share analysis in measuring tourism industry's performance in South Carolina / Tarik Doǧru and Ercan Sirakaya-Turk -- 11. Destination attractiveness based on supply and demand evaluations / Sandro Formica and Muzaffer Uysal -- 12. Overbooking research in the lodging industry : from origins in airlines to what lies ahead / Matthew Krawczyk, Timothy Webb, Zvi Schwartz, and Muzaffer Uysal -- 13. Evaluating forecasting performance : accuracy measures and their application in hospitality / Larissa Koupriouchina, Jean-Pierre van der Rest, Zvi Schwartz, and Dirk Sierag -- 14. Frontier approaches for performance measurement in the hospitality and tourism industries / Albert Assaf and Frank Wogbe Agbola -- 15. Managing tourist satisfaction : an index approach / Jason Li Chen, Gang Li, and Haiyan Song -- 16. Toward increased accuracy in productivity measurement : evidence-based analytics / Cherylynn Becker -- 17. Performance measures and use in hospitalit
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Hospitality industry -- Management; Tourism -- Management; Hospitality industry -- Management; Tourism -- Management; BUSINESS & ECONOMICS / Small Business; elektronické knihy; electronic books